2021
DOI: 10.21307/stattrans-2021-010
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy prediction of small- and medium-sized enterprises in Poland based on the LDA and SVM methods

Abstract: The impact the last financial crisis had on the small- and medium-sized enterprises (SMEs) sector varied across countries, affecting them on different levels and to a different extent. The economic situation in Poland during and after the financial crisis was quite stable compared to other EU member states. SMEs represent one of the most important segments of the economy of every country. Therefore, it is crucial to develop a prediction model which easily adapts to the characteristics of SMEs. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Ptak-Chmielewska built a bankruptcy prediction model based on the SVM algorithm. By comparing three typical corporate distress models with this model, they concluded that traditional neural network algorithms can effectively predict corporate distress from the perspective of financial statements [ 16 ]. Zhou et al discussed the effectiveness and limitations of SVM when applied to the bankruptcy prediction problem, and the experimental results showed that the SVM method of their classifier performed better than the BPN neural network model on corporate bankruptcy problems, and with the reduction of the training set size, the accuracy and generalization degree of the SVM algorithm are higher than those of the BPN algorithm [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Ptak-Chmielewska built a bankruptcy prediction model based on the SVM algorithm. By comparing three typical corporate distress models with this model, they concluded that traditional neural network algorithms can effectively predict corporate distress from the perspective of financial statements [ 16 ]. Zhou et al discussed the effectiveness and limitations of SVM when applied to the bankruptcy prediction problem, and the experimental results showed that the SVM method of their classifier performed better than the BPN neural network model on corporate bankruptcy problems, and with the reduction of the training set size, the accuracy and generalization degree of the SVM algorithm are higher than those of the BPN algorithm [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Then, the XGB based classification optimized using JO method named JO XGB is utilized for classifying the financial data. In Ptak-Chmielewska [16], compared the efficiency of LDA and SVM predictions. An instance of SME was utilized in the empirical analyses, financial ratios have been used and non-financial aspects have been considered.…”
Section: Prior Fcp Models For Smesmentioning
confidence: 99%
“…In recent years, Brozyna's team has used classic regression models and other methods to predict the bankruptcy of enterprises in individual industries with relatively accurate results [20]. Ptak-Chmielewska compared the validity of LDA and SVM predictions using Polish SMEs as a case study [21]. Kitowsk's research team selected 50 companies in Poland to verify the international applicability of the traditional Logit model [22].…”
Section: Introductionmentioning
confidence: 99%